2019
DOI: 10.1016/j.apmr.2019.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition Impairments in the Long Term Post Stroke

Abstract: Objective: To examine the presence of social cognition deficits and the relationship between social and general cognition (eg, attention, mental speed, verbal, visual, or memory abilities) in a large sample of chronic stroke patients and to identify stroke-related factors associated with social cognitive performance. Design: Inception cohort study in which social cognition was assessed at 3-4 years post stroke. Setting: Stroke units in 6 general hospitals. Participants: The data of 148 patients were availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 30 publications
5
35
1
Order By: Relevance
“…USER-P restriction scores were indeed higher in a sample with greater stroke severity (Groeneveld et al, 2019). Social cognitive deficits were mild as well; even though patients scored significantly lower compared to controls on emotion recognition, ToM and behavioural control, effect sizes were only small (Nijsse et al, 2019b) and a maximum of only 4.2% of the patients were impaired to a degree of two standard deviations or more below control mean. Support for the role of stroke severity in the relationship of social cognition and participation is found in the fact that social cognition does not predict community participation in healthy controls (Pijnenborg et al, 2009) and that studies reporting a relationship in TBI patients involved participants with moderate to severe TBI (Knox & Douglas, 2009;May et al, 2017;Struchen et al, 2008;Ubukata et al, 2014;Westerhof-Evers et al, 2018).…”
Section: Bivariate Analysesmentioning
confidence: 81%
See 2 more Smart Citations
“…USER-P restriction scores were indeed higher in a sample with greater stroke severity (Groeneveld et al, 2019). Social cognitive deficits were mild as well; even though patients scored significantly lower compared to controls on emotion recognition, ToM and behavioural control, effect sizes were only small (Nijsse et al, 2019b) and a maximum of only 4.2% of the patients were impaired to a degree of two standard deviations or more below control mean. Support for the role of stroke severity in the relationship of social cognition and participation is found in the fact that social cognition does not predict community participation in healthy controls (Pijnenborg et al, 2009) and that studies reporting a relationship in TBI patients involved participants with moderate to severe TBI (Knox & Douglas, 2009;May et al, 2017;Struchen et al, 2008;Ubukata et al, 2014;Westerhof-Evers et al, 2018).…”
Section: Bivariate Analysesmentioning
confidence: 81%
“…The mean scores on social cognitive tasks and the comparison with the performance of healthy controls have been described elsewhere (see Nijsse et al, 2019b). Briefly, differences between patients and healthy controls were small but significant for the FEEST, Cartoon Test and Hayling test.…”
Section: Social Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Moreover, little is known about the way emotion recognition is related to general cognitive functioning shortly after ischemic stroke. One recent study of social cognition in the long term after ischemic stroke showed only weak associations between other aspects of cognitive functioning and social cognition, 24 but whether these associations are present in the subacute phase is unclear. It is important to study the association between emotion recognition and general cognitive functioning, because impairments of emotion recognition might be explained by general cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
“…There is no time restriction for answering. Total score ranges from 0 to 60, the separate emotion scores range from 0 to 10The FEEST has shown to have good reliability and validity and has proven to be sensitive in various patient groups, such as acquired brain injury patients [ 10 , 51 ] and patients with FTD [ 14 ].…”
Section: Methodsmentioning
confidence: 99%